Analysis of radionuclides and radiation hazards in soil, sediment, water, and rock in Sylhet, Bangladesh - Orthi, Khairum Haque; Sultana, Thuheda; Ferdous, Jannatul; Siraz, Mia Mohammad Mahfuz; Hannan, Abdul (Radiation protection dosimetry, 2025)
The natural radioactivity level in soil, sediment, and water samples collected from the Bisnakandi region in Sylhet was measured using a high-purity germanium detector. The mean activity concentrations of radionuclides in samples from the Bisnakandi were: 232Th (surface soil: 28.60 ± 6.44 Bq/kg, depth soil: 34.97 ± 7.37 Bq/kg, sediment: 41.70 ± 8.22 Bq/kg, water: 16.37 ± 2.13 Bq/L), 226Ra (surface soil: 33.70 ± 6.85 Bq/kg, depth soil: 40.09 ± 8.06 Bq/kg, sediment: 47.60 ± 9.38 Bq/kg, water: 19.76 ± 3.16 Bq/L), and 40K (surface soil: 304.60 ± 20 Bq/kg, depth soil: 375 ± 23.10 Bq/kg, sediment: 455.80 ± 19.2 Bq/kg, water: 241 ± 19.70 Bq/L). The average activity concentrations in rock samples for 232Th, 226Ra, and 40K in (Jaflong, Bholagonj) were (45.69 ± 14.32 Bq/kg, 40.06 ± 12.71 Bq/kg), (36.27 ± 16.89 Bq/kg, 36.84 ± 13.02 Bq/kg), and (430.34 ± 36.82 Bq/kg, 426.7 ± 78.98 Bq/kg), respectively. All the hazard parameters, such as radium equivalent activity, absorbed dose, annual effective dose, and external hazard index, were found within the acceptable level recommended by international organizations.